Facile Synthesis of Carbon Quantum Dots by Plasma-liquid Interaction Method - Tung, Do Hoang; Thuong, Tran Thi; Cong, Nguyen Dinh; Liem, Nguyen Thanh; Kha, Nguyen Van; Manh, Le Hong; Minh, Pham Hong; Thuy, Nguyen Thi Thu; Hoa, Nguyen Minh; Phu, Nguyen Van (Communications in Physics, 2018)
Carbon quantum dots (CQDs) are a novel type of fluorescent nano-materials with various unique properties. They are recently attracting enormous interest due to their superiority in water solubility, chemical inertness, low toxicity, ease of functionalization as well as resistance to photo-bleaching and potential applications in biomedical indication, photo-catalysis, energy conversion, optoelectronics, and sensing. In this work, we present a facile and environmentally friendly synthesis of CQDs based on plasma - liquid interaction method. This is a single-step method and does not use toxic chemicals. The size distribution of obtained CQDs is rather uniform at approximately 3 nm. The emission peak of CQDs shifts from 427 nm to 523 nm as the excitation wavelength is varied from 340 nm to 460 nm. The non-equilibrium reactive chemistry of plasma liquid interaction is responsible for acceleration of the CQDs formation process.